2015
DOI: 10.1186/s13037-015-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the WHO “Safe Surgery Saves Lives” checklist in a podiatric surgery unit in Spain: a single-center retrospective observational study

Abstract: BackgroundThe Surgical Safety Checklist (SSC) is a tool developed by the World Health Alliance for Patient Safety, to assist health professionals in improving patient safety during surgery. Numerous specialties have incorporated this into their clinical practice. The purpose of this study is to adapt and implement this tool within the field of podiatric surgery and to evaluate its impact upon safety standards and post-surgical complications.MethodsAn analytical, observational, longitudinal study has been perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The same clinic carried out all the surgical procedures of the hallux and the other clinic did the mediators of the study variables with a clinical and photographic follow-up. The surgical verification list was used to improve the patients' safety [18].…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…The same clinic carried out all the surgical procedures of the hallux and the other clinic did the mediators of the study variables with a clinical and photographic follow-up. The surgical verification list was used to improve the patients' safety [18].…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…However, findings from previous studies in this area [ 22 25 ] suggest that checklist implementation does not always equate to compliance. In fact, two studies [ 24 , 26 ] found that despite 100 % documented completion of the sign in phase of the checklist, most of the individual items were either not addressed as intended, or not addressed at all.…”
Section: Introductionmentioning
confidence: 96%
“…The third challenge, launched in 2017, "Medication Without Harm" aims to reduce harm related to medications by encouraging institutions to make their systems safer. Brazil, as a member of the WHO, has adhered to all challenges and has been working on improving health care (2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%